SELF-REPRESENTATION AND SYMBOLIC INTERACTIONISM IN THE GAY COMMUNITY IN JAKARTA - Muhammad Iqbal Alif Oktrianda; Citra Eka Putri; Wahyu Srisadono (Universitas prof. Dr. Moestopo (Beragama), 2022)
Indonesia as a country that has a high level of heterogeneity in society, high heterogeneity encourages the emergence of the LGBT phenomenon. Gay belonging to the LGBT group is considered a deviant group by the Indonesian people. This makes the number of verbal and non-verbal rejections that affect the limited interaction of the gay community with the wider community. Based on the above context, the purpose of this study is to find out how the symbolic interactionism of gay community communication on its self-representation. This study uses the phenomenological method on 4 research subjects where 2 of them are gay and the other 2 are communication experts and psychologists. The theory used in this study is the symbolic interactionism theory of George Herbert Mead and Blummer and the representation theory of Stuart Hall. The result of this research is that the symbolic interactionism used by the gay community in the wider community can be used as a tool to represent themselves, non-verbally used by gays is conveyed through slang language, body gestures, accessories, colors and clothing models. sometimes heterosexuals use gay identical symbols unintentionally so that the identical gay symbols become biased.